The Pancasila Guidelines Bill and Ideological Contestation in Indonesia - Happy David Pradhan; Agus Tinus (Department of Government Studies Universitas Muhammadiyah Makassar, 2021)
This discursive article based on secondary sources attempts a discourse analysis of a recently proposed legislation in Indonesia to delineate the contours of ideological contestation between the proponents of the Statist Ideology of Pancasila, and the revival of challenges to it from religious radicalism. By tracing the history of the confrontation between contending ideological conceptions of the Indonesian State, and contextualizing it, through the sociological jurisprudential approach, to the recently proposed, and subsequently postponed, Pancasila Guidelines Bill, 2020, an attempt has been made to decipher the undercurrents of the struggle for sociopolitical hegemony that drive the imperatives in Indonesian polity. The implicit negotiation of interests between the Statist political elites, the civil nationalist religious clergy and the couched praetorian military about the relevance and status of Pancasila as the State Ideology of Indonesia, as outlined in the proposed statute, is taken to be reflective of the challenges confronting, and choices available to the future direction of democracy and inclusivity in Indonesia in the face of growing religious radicalism threatening democratic stability.